Heart Talk: Preventing and Coping with Silrnt and Painful Heart Disease - Cohn P. F.; Cohn J. K. (Boston San Diego New York Harcourt Brace Jovanovich, Publishers, 1987)
From the inside flap: This week - and every week - one thousand Americans will die suddenly of silent heart disease, without pain or warning. How can doctors detect a disease with no symptoms? What immediate preventive measures can you take to better your chances of avoiding heart disease? Are you at risk? HEART TALK answers these questions in a clear and nontechnical manner. The authors evaluate the role of smoking, cholesterol, stress, diet, and exercise in heart health. They explain methods of detection and prevention, discuss treatment, and examine the psychological factors involved in dealing with serious heart disease. Included are a week's worth of tasty, healthful, easy dinner menus avoiding ingredients that promote heart disease. HEART TALK is essential reading for everyone. It will make you healthier - it could save your life.
Keywords: 61